XRF core scanning data of the Pauzhetka tephra intervals in sediment cores from the subarctic Northwest Pacific - Weng-si Chao; Lara Jacobi; Dirk Nürnberg; Ralf Tiedemann; Lester Lembke-Jene (PANGAEA, 2023)
A meridional transect of deep sea sediment cores from the subarctic Northwest Pacific were retrieved from the Emperor Seamount Chain during cruises SO264 in 2018. Several key records were selected and XRF-scanned for initial tephra identification, especially for the Pauzhetka tephra interval(s). The XRF-scanning measurements were carried out with an Avaatech XRF core scanner at the AWI in Bremerhaven. The X-ray excitation scanning settings were 10 kV at 150 mA with no filter for a count time of 10 s, and a rhodium target X-ray tube was deployed. The sample distance was 10 mm, with a 10x12 mm slit size.